Marketing strategy : Based on first principles and data analytics - Palmatier, Robert W. (Red Globe Press, 2017)
This is a brand new textbook on marketing strategy that focuses on the pursuit of solutions to four fundamental marketing problems: All customers differ, all customers change, all competitors react, all resources are limited